Independent Predictors of Mortality Among Patients With NAFLD Hospitalized With COVID‐19 Infection. Issue 11 (24th August 2021) - Younossi, Zobair M.; Stepanova, Maria; Lam, Brian; Cable, Rebecca; Felix, Sean; Jeffers, Thomas; Younossi, Elena; Pham, Huong; Srishord, Manirath; Austin, Patrick; Estep, Michael; Terra, Kathy; et al.
Abstract : The impact of the coronavirus disease 2019 (COVID‐19) pandemic among patients with chronic liver disease is unknown. Given the high prevalence of nonalcoholic fatty liver disease (NAFLD), we determined the predictors of mortality and hospital resource use among patients with NAFLD admitted with COVID‐19 by using electronic medical records data for adult patients with COVID‐19 hospitalized in a multihospital health system who were discharged between March and December 2020. NAFLD was diagnosed by imaging or liver biopsy without other liver diseases. Charlson's comorbidity index (CCI) and Elixhauser comorbidity index (ECI) scores were calculated. In the study sample, among the 4, 835 patients hospitalized for COVID‐19, 553 had NAFLD (age: 55 ± 16 years, 51% male, 17% White, 11% Black, 58% Hispanic, 8% Asian, 5% from congregated living, 58% obese, 15% morbid obesity [body mass index ≥ 40], 51% type 2 diabetes, 63% hypertension, mean [SD] baseline CCI of 3.9 [3.2], and baseline ECI of 13.4 [11.3]). On admission, patients with NAFLD had more respiratory symptoms, higher body temperature and heart rate, higher alanine aminotransferase and aspartate aminotransferase than non‐NAFLD controls (n = 2, 736; P < 0.05). Of the patients with NAFLD infected with COVID‐19, 3.9% experienced acute liver injury. The NAFLD group had significantly longer length of stay, intensive care unit use, and mechanical ventilation, with a crude inpatient mortality rate of 11%. In multivariate analysis, independent predictors of inpatient mortality among patients with NAFLD infected with COVID‐19 were older age, morbid obesity, ECI score ≥ 11, higher Fibrosis‐4 Index (FIB‐4) score, and oxygen saturation <90% (all P < 0.05), but not sex, race/ethnicity, or any individual comorbidity (all P > 0.05). Conclusion: Patients with NAFLD infected with COVID‐19 tend to be sicker on admission and require more hospital resource use. Independent predictors of mortality included higher FIB‐4 and multimorbidity scores, morbid obesity, older age, and hypoxemia on admission.